Phisyological and biochemical factors in predicting outcome in severe community-acquired pneumonia - Spasovska, Katerina; Milenkovikj, Zvonko; Grozdanovski, Krsto (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2008)
The aim of our study was to identify physiologic and biochemical parameters of the patients on admission to hospital that will predict the death from severe community-acquired pneumonia. The study is a retrospective evaluation of patients with clinically and radiologically diagnosed community-acquired pneumonia, treated in the Intensive Care Unit of the Clinic for Infectious Diseases, Skopje, Macedonia in the period between 2003-2005. Eighty-one patients were included in the study, divided in two groups: group A - survivors and group B - non-survivors. Age, gender, symptoms before admission, co-morbidity, tobacco smoking, body temperature, heart rate, respiratory rate, arterial blood pressure, leukocytes count, haematocrit, glycemia, urea, sodium, serum albumen and arterial oxygen saturation were measured in each patient on admission. Results: Twenty-nine (35,8%) of all analyzed patients died, with mean age 63,1±17,9. From patients who died, 19 (43,2%) were males. Smoking, heart rate > 90/min, tachipnea ≥ 25/min., body temperature > 38, 5°C, leucocytes count > 10x10 9/L, uremia >7,4mmol/L and hypoxemia <90% were significantly associated with death on admission of patients with severe community-acquired pneumonia. In conclusion, severe community-acquired pneumonia is a serious life-threatening infection with high mortality. Identifying factors that predict adverse outcome on admission of the patients will contribute in undertaking appropriate treatment and management of this disease.
Keywords: severe community-acquired pneumonia; outcome; predicting factors